Needs Analysis of ELT Materials for Economic Department Students at UIN Alauddin Makassar - Hadi, Arpina; Nurpahmi, Sitti (Universitas islam Negeri Alauddin Makassar, 2023)
The research aims to find out the types of needs for Economic Department ELT Material at UIN Alauddin Makassar and the goals and objectives were formulated from the needs inventory. The research design used in this study was the survey method, the data were obtained from the students’ needs. The research involved 100 respondents which consist of 96 students, were classified into four groups, namely, 27 students who were taken in semester one, 25 students from semester three, 23 students from semester five, and 21 students from semester seven, 2 lecturers, and 2 graduates, from Economics department at UIN Alauddin Makassar. In collecting the data, the used instruments were the questionnaire and interviews for students, graduates, and lecturers. The collection of the data was done by distributing the questionnaires to the participants to identify the students’ needs in Economics Department and interview guideline was used to find out additional data. The researcher involved two activities; distributing the questionnaire to the participant and processing the data derived from the questionnaire and interview. The findings revealed of the research showed the types of students’ needs and the goals and objectives. First, the types of students’ needs analysis consisted of linguistic needs and learning needs. Then, in the linguistic needs part, there are two types of information namely learning ability and learning a priority. Students’ levels are vocabulary, writing, reading, listening, speaking, and grammar. For students learning priorities are vocabulary, reading, speaking, listening, grammar and writing. Then, in the learning parts, there are two types of information, namely learning problems and learning styles. There are two problems that are experienced by students, namely the psychological problems and limited linguistic. And learning styles that students’ needs are auditory, visual, and games. From the analysis result of that information, the needs inventory is found which is used to formulated goals and objectives of English learning in the Economic Department.